Tom's afraid of the dark! - Robbins, Beth.; Stuart, Jon (New York : Dorling Kindersley Pub., 2001)
Tom, a young cat, overcomes his fear of the dark by using his imagination to think about good things rather than bad ones.
Keywords: Fear of the dark -- Fiction; Bedtime -- Fiction; Imagination -- Fiction; Cats -- Fiction